P-43 Palliative care for prisoners: a partnership approach. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Kemp, Rachel; Milton, Libby; Michie, Gerald; Wotherspoon, Angela
Abstract : Background: Supporting our hospice Widening Access agenda, we have developed a partnership with our local prison, HMP Edinburgh. With one of the highest populations of older, long term prisoners in Scotland, there are specific challenges to ensure high quality palliative and end of life care for this group. Barriers include: Identification of prisoners with palliative care needs; Lack of 24/7 health care; Timely access to medication; Prison environment and regime; Staff confidence and competence; Some high risk offenders may not be eligible for compassionate release. Aim: To transform the experience of palliative care for prisoners through a partnership approach with prison, health and palliative care staff, by: Proactive identification of those with palliative care needs Appropriate assessment and management plans Planning ahead to ensure palliative care needs can be safely and effectively met in the hospice or the prison Support for staff Address barriers to providing end of life care Access to medication Out of hours health and social care support. Approaches: Clinical: Hospice clinical nurse specialist attendance at monthly prison healthcare meetings; Individualised review and plans for each prisoner with palliative care needs. Educational: Hospice staff delivery of 'toolbox' talks for prison staff; Identification of link staff at each site. Cultural shift: Build relationships and nurture understanding in both hospice and prison setting; Hospice staff visits to prison with reflective learning sessions; Quarterly strategic meetings with hospice, Marie Curie Nursing Service, NHS and Scottish Prison Service to continue partnership working. Outcomes: Hospice staff attend prison palliative care meeting Prisoners with complex needs referred to specialist service Plans in development to access out of hours nursing care and medication Commitment to ongoing development work Hospice staff supportive and confident to look after prisoners Partnership with prison viewed by charity as an opportunity not a threat.